Watering Your Florida Lawn - Laurie E. Trenholm; Joseph B. Unruh; John L. Cisar (EDIS)
Irrigation is one of the most important cultural practices that we do for our lawns. Since water is a limited resource and is vital to the health of your lawn, it is very important that watering be done correctly. This 3-page fact sheet was written by L. E. Trenholm, J. B. Unruh, and J. L. Cisar, and published by the UF Department of Environmental Horticulture, April 2013.